Contemporary management : - George, Jennifer M. (McGraw Hill, 2006)
Contemporary Management is a comprehensive text that surveys the theoretical underpinnings of modern management thought and research. Through a variety of real world examples from small, medium, and large companies it shows the reader how those ideas are used by practicing managers. While the organization of this text follows the mainstream functional approach of planning, organizing, leading, and controlling its chapters can be used flexibly and instructors can organize their management course according to the format they are most comfortable with. One of the most popular features of the book has always been its focus on the "Manager as a Person," which discusses managers as real people with their own personalities, strengths, weaknesses, opportunities, and problems. In the 4th Edition, the authors expand on this theme by discussing the importance of management competencies- the specific set of skills, abilities, and experiences that gives one manager the ability to perform at a higher level than another in a specific context.